Satyagraha opera in three acts - Glass, Philip 1937- (The Met: Live in HD, 2020)
The Metropolitan Opera Orchestra and Chorus under the direction of Dante Anzolini, perform Philip Glass's opera. Tenor Richard Croft, in the role of Gandhi, leads the stellar cast in a depiction of Gandhi's years in South Africa, during which he developed all his tools for social transformation through non-violence. Filmed during the 2011 production as part of the Met Opera's Live in HD Series